Electricity production and bacterial communities of microbial fuel cell supplied with oily sludge. Issue 5 (12th February 2020) - Guo, Haiying; Xie, Shuixiang; Deng, Hao; Geng, Xiaoheng; Wang, Penghua; Huang, Chunfeng; Tang, Shanfa
Abstract: Oily sludge is a major problem affecting the quality of oil fields and surrounding environment. Microbial fuel cell (MFC) technology is a simple way to treat the oily sludge while generating electricity. To investigate the electrochemical properties of such MFC and the characteristics of bacteria attached to anode, a single‐chamber MFC supplemented with oily sludge was constructed. The electrochemical results showed that the oily sludge is suitable for MFC operation, with a maximum output voltage of 299.13 mV and a maximum output power ( P max ) of 2, 255.52 mW/m 2 . The cyclic voltammetry curve of MFC anode displayed an "S" shape, whereas the main peaks were at 0 and 0.1 V, indicating a strong redox reaction on the anode carbon felt. The limiting current was 0.08 A/cm 2 . The scanning electron microscopy (SEM) of the bacteria on the anode surface showed that most of bacteria displayed a rod‐shaped morphology, whereas the biological metagenomic classification sequencing showed that the predominant electricity‐producing bacteria were Proteiniciclasticum (15.83%) from Firmicutes and Pseudomonas (11.9%) from Gammaproteobacteria. MFC can effectively utilize the oily sludge to generate electricity at the same time, which provides a theoretical basis for the research of MFCs' pollution control and electricity production.